2020
DOI: 10.1186/s12873-020-00386-z
|View full text |Cite
|
Sign up to set email alerts
|

Propensity score adjusted comparison of three-factor versus four-factor prothrombin complex concentrate for emergent warfarin reversal: a retrospective cohort study

Abstract: Background Prothrombin Complex Concentrates (PCC) are prescribed for emergent warfarin reversal (EWR). The comparative effectiveness and safety among PCC products are not fully understood. Methods Patients in an academic level one trauma center who received PCC3 or PCC4 for EWR were identified. Patient characteristics, PCC dose and time of dose, pre- and post-INR and time of measurement, fresh frozen plasma and vitamin K doses, and patient outcomes were collected. Patients whose pre-PCC International Normaliz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Of the remainder, 15 were selected based on inclusion and exclusion criteria for the qualitative synthesis (systematic review). Three of these 15 were excluded [21,29,34], leaving 12 included [20,[22][23][24][25][26][27][28][30][31][32][33] for the quantitative synthesis (meta-analysis). A PRISMA ow diagram of study inclusion is shown in Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the remainder, 15 were selected based on inclusion and exclusion criteria for the qualitative synthesis (systematic review). Three of these 15 were excluded [21,29,34], leaving 12 included [20,[22][23][24][25][26][27][28][30][31][32][33] for the quantitative synthesis (meta-analysis). A PRISMA ow diagram of study inclusion is shown in Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Reversal to INR goal was limited to the warfarin group in this study. Another study was primarily concerned with non-warfarin-related coagulopathy; however, the results from patients on warfarin reversed with PCCs were still extracted [32].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations